20 jaar Gallery De Gryse. - De Gryse, Ghislaine; Van Buynder, Ernest (Tielt : Gallery De Gryse, 1995)
Bert, Lore ; Blocher, Sylvie ; Bourgeois, Louise ; Fortuyn/O'Brien ; Freund, Gisèle ; Hoekman, Mirjam ; Horn, Rebecca ; Kwaaitaal, Daniëlle ; Keeley, Shelagh ; Lafont, Suzanne ; Lafontaine, Marie-Jo ; Liv, Lena ; Maes, Agnes ; Pacquée, Ria ; Schouten, Lydia ; Simoni, Mariella ; Spilliaert, Rozemarijn ; Siepman van den Berg, Eja ; Van Kerckhoven, Anne-Mie ; Vertessen, Liliane
biografie
20 jaar / year Gallery, Gallery De Gryse, Tielt, 22/10/1995 - 10/12/95
Text Dutch-English
kunstcatalogus